2014
DOI: 10.11138/ads/2014.5.2.052
|View full text |Cite
|
Sign up to set email alerts
|

Tooth wear among patients suffering from mental disorders

Abstract: SummaryAim. Assess oral health, treatment needs and the correlation between tooth wear and medications in patients with psychiatric disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Though we did not attempt to measure the proportion with anxiety and/or depression within HIV + ve and HIV-ve subject groups, our findings suggest this population is more affected by psychiatric disorders than non-infected individuals. Furthermore, those with HIV presented with both psychiatric disorders and tooth wear, which agrees with the findings of Piccoli et al [23], who suggested that individuals with depression and anxiety have increased tooth wear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though we did not attempt to measure the proportion with anxiety and/or depression within HIV + ve and HIV-ve subject groups, our findings suggest this population is more affected by psychiatric disorders than non-infected individuals. Furthermore, those with HIV presented with both psychiatric disorders and tooth wear, which agrees with the findings of Piccoli et al [23], who suggested that individuals with depression and anxiety have increased tooth wear.…”
Section: Discussionsupporting
confidence: 90%
“…Both depression and anxiety affect a person’s quality of life [5, 34] as well as their ability to follow the treatment regimen for HIV and attend to their oral self-care [3, 15, 25]. The presence of psychological disorders is known to result in various oral health problems, such as bruxism [6, 21] and tooth wear [23]. Several researchers found bruxers to have increased incidence of anxiety than non-bruxers [12, 16].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Physical wearing of the tooth surface through an abnormal mechanical process which is independent of occlusion is called as “abrasion.” It involves the presence of a foreign object or a substance which is repeatedly in contact with the tooth. [4] The last few decades have shown a general improvement in the oral hygiene status of individuals due to an increased dental awareness.…”
Section: Introductionmentioning
confidence: 99%
“…The surface loss of tooth structure from causes other than dental caries, trauma, or as a result of developmental disorders has been termed as “tooth wear.”[ 2 ] Tooth wear is a complex, multifactorial phenomenon with the interplay of biological, mechanical, chemical, and tribological factors. [ 3 ] Physical wearing of the tooth surface through an abnormal mechanical process which is independent of occlusion is called as “abrasion.” It involves the presence of a foreign object or a substance which is repeatedly in contact with the tooth. [ 4 ] The last few decades have shown a general improvement in the oral hygiene status of individuals due to an increased dental awareness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the single or combined effects of the psychotropic drugs, the detorioration of the stomatognathic apparatus among psychiatric patients may be precipitated by the impaired social and cognitive functioning resulting in a relative poor quality of life 6,8,10 . It has also been suggested that bruxism may be associated with emotional tension, psychosomatic disorders, hostility, aggressiveness, apprehension and a tendency to worrying, as well as with psychiatric disorders [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%